(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
If we deploy a long-term historical perspective, we notice that most of the ages have established a steady mix of orality and writing, beginning with the Omero’s poems. The sharp dichotomy between orality and writing, one of the ‘binarisms’ on which the Western culture was built, has long been abandoned: in our age there is, more than anything else, a convergence of different communication channels, a sensorial synaesthetic cooperation, or, again, an hybridization. Due to this continuous interaction between the two levels, in literature we find often a mimesis of orality, which can configure itself, from time to time, as nostalgia for a lost origin, evocation, or pure performative effect.